Anthropometric Measurement and Analysis of Infants and Toddlers in Laucih Village, Medan Tuntungan District in the 2026 Inkessumut Community Service Framework - Meta Agrifina; Riska Annisa Sitepu; Astriana Fransiska Butarbutar; Sari Saraswati Purba; Yohana Tetty Gultom (Outline Journal of Community Development, 2026)
Nutritional problems among infants and toddlers remain a significant concern in Indonesia’s health development, particularly in areas with limited access to health information and services. This community service activity aimed to conduct anthropometric measurements as an early detection strategy for assessing the nutritional status of infants and toddlers, as well as to provide nutrition education for parents in Laucih Village, Medan Tuntungan District. The activity was carried out by lecturers and students of the Bachelor of Nutrition Study Program at the North Sumatra Institute of Health (INKESSUMUT) as part of the 2026 Community Service Program organized by the Institute for Research and Community Service (LPPM) of INKESSUMUT. The implementation method involved measuring body weight, body height/length, and mid–upper arm circumference (MUAC) of 10 toddlers using WHO-standardized measuring instruments. The collected data were analyzed using the WHO Z-score reference to determine nutritional status. In addition to anthropometric assessment, nutrition education was provided to mothers of toddlers, focusing on the importance of balanced nutrition, appropriate feeding practices, and routine growth monitoring through Posyandu services. The results showed that among the 10 toddlers assessed, 60% had normal nutritional status, while 40% were classified as being at risk of stunting. Notably, one child within the stunting-risk group was also identified as having undernutrition. These findings indicate that, although the majority of toddlers exhibited normal nutritional status, a substantial proportion remains vulnerable to growth-related nutritional problems. This underscores the need for continuous and sustainable community service initiatives with a more integrated approach, including capacity building for community health cadres and the use of local data to support targeted nutrition intervention planning.